A method of treating discoloration in persons associated with exposure to harmful industrial factors - O. A. Uspenskaya; L. Ya. Nikulicheva; A. S. Klochkov (Эндодонтия Today)
INTRODUCTION. The search for the optimal bleaching method that minimizes the side effects of bleaching and prolongs the result of bleaching is an urgent task of dentistry.AIM. To study the effectiveness of the method of treating discoloritis in people exposed to harmful industrial factors.MATERIALS AND METHODS. 40 somatically healthy patients aged 23 to 45 years old, working at the plant, with harmful production factors, were identified. Of these, 22 were women and 18 were men who had teeth whitening. Tooth shade was determined using the VITA SYSTEM 3D-MASTER® scale before, after, 14 days, 3, 6, 12 months after bleaching.RESULTS. Examination of patients before the procedure of professional teeth whitening revealed the absence of hyperesthesia in all subjects (100 %), immediately after bleaching, the appearance of hypersensitivity in all patients was noted, based on clinical examination data and dynamics of the values of the IIGZ, IRGZ, Schiff and VAS indices, which creates the need for the use of remineralizing in persons working in hazardous production therapy. The assessment of the color shade of teeth after whitening revealed a change in color intensity in 100 % of cases, while the change in color lightness on the VITA SYSTEM 3D-MASTER scale was 1–2 steps. The use of the infiltration method after bleaching led to the restoration of the structure of hard tissues.CONCLUSION. The conducted research indicates the appearance of 100 % dental hyperesthesia during the professional whitening procedure in persons exposed to harmful industrial factors.